Recent Developments in Game-Based Virtual Reality Educational Laboratories Using the Microsoft Kinect - Zhang, Mingshao; Zhang, Zhou; Chang, Yizhe; Aziz, El-Sayed; Esche, Sven; Chassapis, Constantin (International journal of emerging technologies in learning, 2018)
Virtual Reality (VR) is a well-known concept and has been proven to be beneficial in various areas. However, several disadvantages inherent in VR prevent its broad deployment in the educational arena. These limitations include non-realistic representation, lack of customizability and flexibility, financial feasibility, physical and psychological discomforts of the users, simulator sickness, etc. In this paper, an innovative method that uses the Microsoft Kinect as an essential component for developing game-based VR educational laboratories is presented. This technique addresses three different aspects. First, it represents an efficient method for creating the VE using the Kinect as a measuring tool. Second, the Kinect is employed as a substitute DAQ system for acquiring range data and tracking the motion of objects of interest. At last, the Kinect serves as a novel human-computer interface for tracking the users’ entire body motion and recognizing their voices. Using the method described here, three major aspects of educational VR development can be accomplished with an inexpensive and commercially available Kinect.